On the Berezin number of operators on the reproducing kernel of Hilbert space and related questions - Yamancı, Ulaş; Karlı, Ismail M. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.956 We obtain some new inequalities for the Berezin number of operators via the Cauchy–Schwarz-type inequalities. Some other related questions are also discussed.